Improving fistula data reporting through collaboration, learning and adaptation of fistula tools and indicators in Uganda - Kanakulya, Hassan; Kaduyu, Paul; Arnoff, Elly; Mukisa, Rose; Tripathi, Vandana (Nepal Journal of Obstetrics and Gynaecology, 2018)
Aims: To report on efforts to improve fistula service statistics reporting in Uganda. Methods: A process review assessed the adoption of fistula tools and indicators nationally and in four districts. In addition to HMIS/DHIS2 data review, nine key informant interviews were conducted, at two district hospitals, two specialized hospitals and with the national senior biostatistician. Results: Two of four were included in the revised HMIS/DHIS2 and three of four hospitals were using standardized fistula tools. From July 2017- June 2018, 595 repairs and 310 fistula cases were reported into DHIS2 and evidence of data use at the district level. However, there was low reporting rate for fistula data, due to low awareness of the new HMIS indicators. Conclusions: Integration of the fistula and obstetrics/gynecology registers, refinement of the fistula register, and development of discharge and follow-up registers were considered by partners thus leading to availability of routine data to support planning.